Training impulse and session ratings of perceived exertion as perceived by athletes and observed by coaches during preseason football camp - Smith-Hale, V.; Mendoza, R.; Vargo, C.; Schoen, M.; Jimenez, L.; VanSumeren, M.; Sabourin, J.; Rider, B.; Martin, J.; Moore, E.; Hew-Butler, T. (The Journal of Strength and Conditioning Research, 2025)
Quantification of internal training load (TL), through wearable technology, represents an emerging metric for TL management in sport. The accuracy of subjective vs. objective assessments of TL, as perceived by athletes and observed by coaches, has yet to be evaluated during long-duration football practices (>2 hours). The purpose of this study was to evaluate relationships among objective heart rate (HR) and subjective ratings of perceived exertion (RPE) assessment of TL in collegiate American football athletes, and their coaches, during preseason camp. Twenty-four athletes (first-year, n = 6; returning, n = 18) and 2 coaches (football coach [FBC], n = 1; strength and conditioning coach [SCC], n = 1) participated. Athletes wore chest strap HR monitors during the first 6 days of preseason football camp for an objective TL assessment using training impulse (TRIMP: average exercise HR × duration of practice). Subjective TL was assessed by both athletes (perceived) and coaches (observed) using a session ratings of perceived exertion (sRPE; 0-10 rating scale; 10 = maximum effort). The average practice duration was 142.3 ± 35.5 minutes, with 139 total observations across 6 practices. Significant (alpha level p = 0.05) relationships were noted between TRIMP and sRPE from the athletes (r = 0.62), FBC (r = 0.68) and SCC (r = 0.49). When subdivided into first-year and returning groups, relationships were stronger between TRIMP and sRPE with first-year athletes (athlete r = 0.68; p = 0.001; FBC r = 0.79; p = 0.001; SCC r = 0.64; p = 0.001) than for returning athletes (athlete r = 0.60; p = 0.001; FB coach r = 0.70; p = 0.001; SCC r = 0.40: p = 0.001). These data suggest that subjective athlete perceptions and coach observations of TL are in low-moderate agreement, indicating these are not interchangeable, during long-duration preseason football camp.